The automotive order to delivery process: how should it be configured for different markets? - Brabazon, Philip G.; MacCarthy, Bart L. (Elsevier, 2017)
The order-to-delivery (OTD) process in the volume automotive sector is important for automakers, dealers and customers. It affects the customer's experience with regard to receiving a vehicle that matches their requested specification in a reasonable time and the costs of the automaker in serving the market. OTD processes share similarities across major volume automakers. They are substantial in scale with typically a very large number of vehicle variants and involve interactions between customers, dealers and the automaker. Additionally, automotive markets are heterogeneous. Some customers have little tolerance to compromising on specification and/or waiting for a vehicle whilst others are more tolerant on one or both attributes. This study examines how the OTD process should be configured for different markets. A representative simulation model is used with designed experiments and an innovative statistical analysis method to study the impact of nine OTD configuration factors in three different markets. The study shows that market attributes have a substantial bearing on the dominant modes of fulfillment, on customer-centric performance metrics and on automaker costs. The findings have strong implications for automakers regarding how they configure their OTD processes for different markets and whether they focus on upstream, pre-assembly factors and/or downstream post-assembly factors. This is the first study to use a comprehensive and detailed OTD process model, incorporating a wide range of configuration factors, and assess a full range of performance metrics in a designed simulation study.